PELESTARIAN KESENIAN KOMPANG DI SANGGAR SENI TAPAK BUDAYA TANJUNG UBAN KABUPATEN BINTAN PROVINSI KEPULAUAN RIAU - Galih Rakasiwi; Syeilendra Syeilendra; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2018)
ABSTRACTThis researchaims at observing the function of “Kompang” and describing its preservation from Tapak Budaya art studio in Tanjung Uban, Bintan, Riau Island. This qualitative research applied the descriptive analysis method. The primary instrument was the researcher himself helped with stationaries, note books, and a camera. There were two types data in this research: primary and secondary data. They were later analyzed by reducing, presenting, and verifying data. The research result shows that the art of “Kompang” still remains until today and it is still presented as it was before in the past. The studio developes the volume of the art performance to other regions and does not forbid anyone who is interested in learning the art. They also add new rhymes and develop the motives. The art is always created analog with the condition and needs of the audience. Meanwhile, the function of “Kompang” is as an entertainment for the host and the audiences.Keyword: Pelestarian, Kompang, Sanggar Tapak Budaya.